2004
DOI: 10.1253/circj.68.451
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Interleukin-6 and Matrix Metalloproteinase-9 in the Infarct-Related Coronary Artery of Acute Myocardial Infarction

Abstract: n acute occlusion of coronary artery fails into acute myocardial infarction (AMI) and it is thought that rupture of vulnerable fibrous caps of atherosclerotic plaque is involved. 1,2 Several cytokines, including interleukin-1 (IL-1 ), IL-6 and tumor necrosis factor-(TNF-), may be released from vulnerable plaques, [3][4][5][6] which then activates macrophages. [7][8][9][10] Most studies have investigated the atherosclerotic plaques of experimental animals [8][9][10][11] and there are only a few clinical reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Whereas MMP-9 is released from various cardiac tissue cells including myocytes, 27 endothelial cells, 28 and smooth muscle cells, 16 in the infarcted cardiac tissue it is mainly released from the infiltrating inflammatory cells such as macrophages 16,17,29 and neutrophils. 6,7 Lyndsey et al reported that infiltrating neutrophils were the source of the increased MMP-9 observed in a canine ischemia/reperfusion model.…”
Section: Elevated Proteinase Level As a Marker For Cardiac Tissue Injmentioning
confidence: 99%
“…Whereas MMP-9 is released from various cardiac tissue cells including myocytes, 27 endothelial cells, 28 and smooth muscle cells, 16 in the infarcted cardiac tissue it is mainly released from the infiltrating inflammatory cells such as macrophages 16,17,29 and neutrophils. 6,7 Lyndsey et al reported that infiltrating neutrophils were the source of the increased MMP-9 observed in a canine ischemia/reperfusion model.…”
Section: Elevated Proteinase Level As a Marker For Cardiac Tissue Injmentioning
confidence: 99%
“…7,8 Elevated plasma levels of MMP-9 in the peripheral blood have been shown in patients with ACS, 9 and are associated with severe coronary stenosis 10 and cardiovascular mortality. 11 In addition, the plasma MMP-9 level is elevated in the coronary circulation of patients with ACS, 12,13 indicating that the production of MMP-9 may be enhanced in ACS.MMP release, however, may also occur in the interstitium of ischemic myocardium in the early period after a myocardial infarction (MI), 14 as well as from coronary plaque. The serum MMP concentration is associated with left ventricular remodeling after MI, 15 and in particular, an elevated plasma MMP-9 level is associated with infarct size.…”
mentioning
confidence: 99%
“…7 IL-6 could be synthesized by activated macrophages and with vascular smooth muscle cells infiltrating into the atherosclerotic plaque. [12][13][14][15][16] Mechanical stretch, vascular injury and hypoxia may be involved in causing IL-6 release in the coronary circulation after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6] We demonstrated an increase in regional IL-6 levels in the infarct-related coronary artery in patients with acute myocardial infarction. 7 Recent development of the percutaneous coronary intervention (PCI) technique enables us to rescue patients from acute coronary occlusion. [8][9][10] However, one of the residual problems is restenosis of the coronary artery, which was recanalized by PCI.…”
mentioning
confidence: 99%